2014
DOI: 10.1051/0004-6361/201424303
|View full text |Cite
|
Sign up to set email alerts
|

Formation of S0 galaxies through mergers

Abstract: Context. Observations reveal a strong structural coupling between bulge and disc in S0 galaxies, which seems difficult to explain if they have formed from supposedly catastrophic events such as major mergers. Aims. We face this question by quantifying the bulge-disc coupling in dissipative simulations of major and minor mergers that result in realistic S0s. Methods. We have studied the dissipative N-body binary merger simulations from the GalMer database that give rise to realistic, relaxed E/S0 and S0 remnant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 113 publications
(128 reference statements)
3
63
3
Order By: Relevance
“…In the recent literature, pseudo-and classical bulges have frequently been divided at the Sérsic index n 2 sph = (e.g., Sani et al 2011;Beifiori et al 2012), although, from a selection of hundreds of disk galaxies imaged in the Kband, Graham & Worley (2008) observed no bimodality in the bulge Sérsic indices about n 2 sph = or any other value. While pseudo-bulges are expected to have exponential-like surface brightness profiles (n 1 sph  ), being disky components that formed from their surrounding exponential disks (e.g., Bardeen 1975;Hohl 1975;Combes & Sanders 1981;Combes et al 1990;Pfenniger & Friedli 1991), it has been shown that mergers can create bulges with n 2 sph < (e.g., Eliche-Moral et al 2011;Scannapieco et al 2011;Querejeta et al 2015), just as low-luminosity elliptical galaxies (not built from the secular evolution of a disk) are also well known to have n 2 sph < and even n 1 sph < (e.g., Davies et al 1988;Young & Currie 1994;Jerjen et al 2000). The use of the Sérsic index (in addition to rotation) to identify pseudo-bulges is thus a dangerous practice.…”
Section: Pseudo-versus Classical Bulgesmentioning
confidence: 99%
“…In the recent literature, pseudo-and classical bulges have frequently been divided at the Sérsic index n 2 sph = (e.g., Sani et al 2011;Beifiori et al 2012), although, from a selection of hundreds of disk galaxies imaged in the Kband, Graham & Worley (2008) observed no bimodality in the bulge Sérsic indices about n 2 sph = or any other value. While pseudo-bulges are expected to have exponential-like surface brightness profiles (n 1 sph  ), being disky components that formed from their surrounding exponential disks (e.g., Bardeen 1975;Hohl 1975;Combes & Sanders 1981;Combes et al 1990;Pfenniger & Friedli 1991), it has been shown that mergers can create bulges with n 2 sph < (e.g., Eliche-Moral et al 2011;Scannapieco et al 2011;Querejeta et al 2015), just as low-luminosity elliptical galaxies (not built from the secular evolution of a disk) are also well known to have n 2 sph < and even n 1 sph < (e.g., Davies et al 1988;Young & Currie 1994;Jerjen et al 2000). The use of the Sérsic index (in addition to rotation) to identify pseudo-bulges is thus a dangerous practice.…”
Section: Pseudo-versus Classical Bulgesmentioning
confidence: 99%
“…Specific details on the criteria used to select the sample will be provided elsewhere (Eliche-Moral et al, in prep. ), but Borlaff et al (2014) and Querejeta et al (2015a) contain a summary of how this process is done. Hence, in Sect.…”
Section: Methodsmentioning
confidence: 99%
“…For the K-band images we simulated the conditions of the NearInfraRed S0 Survey (NIRS0S, Laurikainen et al 2011) to perform the comparisons shown in Querejeta et al (2015a). We added photon noise to the model images to have a signal-tonoise ratio (S /N) of 3 for the limiting magnitude of the images.…”
Section: Selection Of S0s In Artificial Photometric Imagesmentioning
confidence: 99%
See 2 more Smart Citations